The Middle Ages : an illustrated history - Hanawalt, Barbara A. (New York : Oxford University Press, 1998)
A history of the Middle Ages, including the merger of Roman, Christian, and Germanic cultures; the transformation of the Roman Empire; and social, economic, religious, and cultural aspects of medieval life.
Includes bibliographical references (p. 152-155) and index.
Keywords: Middle Ages